DNA Sequence Variants and Protein Haplotypes of Casein Genes in German Black Pied Cattle (DSN) - Meier, Saskia; Korkuć, Paula; Arends, Danny; Brockmann, Gudrun A. (Frontiers in Genetics, 2019)
Casein proteins were repeatedly examined for protein polymorphisms and frequencies in diverse cattle breeds. The occurrence of casein variants in Holstein Friesian (HF), the leading dairy breed worldwide, are well known. The frequencies of different casein variants in HF are likely affected by selection for high milk yield. Compared to HF, only little is known about casein variants and their frequencies in German Black Pied cattle (DSN). The DSN population was a main genetic contributor to the current high yielding HF population. The goal of this study was to investigate casein (protein) variants and casein haplotypes in DSN based on the DNA sequence level and to compare these with data from HF and other breeds. In the investigated DSN population we found no variation in the alpha-casein genes CSN1S1 and CSN1S2, and detected only the αS1*B and αS2*A protein variants. For CSN2 and CSN3 genes non-synonymous SNPs leading to three different β and κ protein variants were found, respectively. For β casein protein variants A1, A2 and I were detected, with β*A1 (82.7%) showing the highest frequency. For κ casein protein variants A, B, and E were detected in DSN, with the highest frequency of κ*A (83.3%). Accordingly, the casein protein haplotype αS1*B - β*A1 - αS2*A- κ*A (order of genes on BTA6) is the most frequent haplotype in DSN cattle.